PENGARUH PENERAPAN METODE BERMAIN PERAN (ROLE PLAYING) PADA PEMBELAJARAN AL-QUR’AN HADITS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV MI AL- KARIMAH TANRUNG KECAMATAN AJANGALE KABUPATEN BONE - Ahmad Munawar; Andi Marjuni; Munirah Munirah (Universitas Islam Negeri Alauddin Makassar, 2022)
This study is a quasi-experimental design research that aims to determine the application of the role playing method in learning Al-Qur'an Hadith in class IV MI Al-Karimah Tanrung Kec.Ajangale Kab.Bone, to determine student learning outcomes before and after the role playingmethod was applied to the learning of the Qur'an Hadith in class IV MI Al-Karimah Tanrung Kec.Ajangale Kab.Bone, and to find out the effect of the application of the role playing method on learning the Qur'an 'an Hadith on the learning outcomes of fourth grade students of MI Al-Karimah Tanrung Kec.Ajangale Kab.Bone. The sample taken in this study amounted to 12 students using data collection techniques, namely tests, observations and documentation. Data analysis using simple regression with the help of SPSS 25.0 application. Based on the results ofthe descriptive analysis of the learning outcomes of fourth grade students at MI Al-Karimah Tanrung Kec. Ajangale Kab. Bone average value of Post Test after being processed into SPSS 25.0 is 82.08 and the average value of Pre-test is 64.17. There is an influence of the role playingmethod on learning Al-Qur'an Hadith on the learning outcomes of fourth grade students of MI Al-Karimah Tanrung Kec.Ajangale Kab.Bone. This can be seen in the t-test analysis that has been carried out using simple regression using SPSS showing Thit = 5,750 with Ttable = 2,262. The significance value obtained is smaller than (0.000 > 0.05). With the magnitude of the influence of 76.8% of the test results of the coefficient of determination (R Square).